(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to examine the effect of psychological and motivating factors like entrepreneurial self-efficacy and expectancy value-belief in relation to moderating role of entrepreneurial intention in entrepreneurial success of indigenous business in Surkhet valley. Methods: The research used a quantitative approach, utilizing structured interviews with indigenous entrepreneurs from the Surkhet valley. This study focuses on essential constructs such as self-efficacy in entrepreneurship, value- beliefs related to Psychology, intentions to participate in entrepreneurial endeavors, and measures of entrepreneurial success. Structural Equation Modeling (SEM) was utilized to examine the connections between these constructs. Results: The result of this study demonstrated a favorable and significant impact of expectancy value-belief and entrepreneurial self-efficacy on entrepreneurial intention and entrepreneurial success whereas entrepreneurial self-efficacy has positive but insignificant impact on entrepreneurial success. Conclusion: It concludes that primary and advantageous indicators of business success are entrepreneurial intention and expectation value-belief. Among these, entrepreneurial intention is particularly significant in assessing entrepreneurial success due to its substantial influence